Developing Student Creativity and Independence Through a Deep Learning Approach - Muhammad Aji Ahmadi; Jasmansyah (Institut KH Ahmad Sanusi (INKHAS) Sukabumi, 2026)
The deep learning approach integrating mindful, meaningful, and joyful learning was implemented to address low creativity and independence among grade VIII students in Islamic Religious Education (PAI) at SMP Negeri 4 Kota Sukabumi. This qualitative case study examined: (1) deep learning implementation through four phases (preparation, exploration, application, reflection); (2) creativity enhancement via innovative projects like Islamic values posters and animated videos; and (3) supporting-inhibiting factors. Data were collected through observation, teacher-student interviews, and RPP document analysis aligned with the Merdeka Curriculum. Findings reveal deep learning effectively boosts creativity through akidah akhlak concept exploration and independence through personal reflection journals, supported by teacher commitment but hindered by limited digital facilities. The study provides a replicable deep learning-based PAI model for developing Pancasila student profiles.